Common Radio Resource Management: Joint Call Admission Control And Traffic Offloading Method - Zaini, Khuzairi Mohd (2018)
The concept of Common Radio Resource Management (CRRM) has been proposed by 3GPP in order to efficiently manage the common pool of radio resources that are available for each of the existing radio access technologies in the heterogeneous wireless networks (HWNs). The main challenge of CRRM for HWNs is to search the best connection for the demanded services, enabling calls transference from one interface to another seamlessly and utilizing the availability of all radio resources. Thus, this thesis proposes a joint call admission control (JCAC) and traffic offloading algorithms in the CRRM for an integrated cellular and mobile network. The contributions of this work are threefold. First, a user mobility model in the wireless overlay network is proposed.